Prediksi Pertumbuhan Kota Bandar Lampung menggunakan Model Cellular Automata - M. Panji Agustri; Henky Mayaguezz; Arief Darmawan (Institut Nalanda, 2026)
The rapid growth of Bandar Lampung City is characterized by an increasing conversion of non-built-up land into built-up areas. This condition is influenced by population growth, economic development, and the strategic position of Bandar Lampung as the capital of Lampung Province and the gateway to Sumatra Island. Such development has the potential to create pressure on land use if it is not aligned with the Spatial Plan (RTRW). This study aims to analyze the spatial pattern and distribution of urban growth, and to assess the conformity of urban growth modeling results with the Bandar Lampung Spatial Plan. This research employs a spatial-based quantitative approach. The analytical methods used include the Cellular Automata (CA) modeling to predict urban growth up to 2041 and overlay analysis to evaluate the conformity of the modeling results with the Bandar Lampung Spatial Plan 2021–2041. The results indicate that the built-up area increased from 12,096.93 hectares in 2017 to 12,979.87 hectares in 2023, and is projected to reach 14,758.74 hectares by 2041. Spatially, urban growth tends to concentrate in peripheral areas that still have land availability and good accessibility. The conformity level of built-up land with the spatial plan decreased from 95.17% in 2023 to 89.24% in 2041. These findings indicate the need for stricter and more consistent land use control.